EFFECT OF CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), NON PERFORMING LOAN (NPL) AND OPERATIONS EXPENSES TO OPERATIONS INCOME (BOPO) ON RETURN ON ASSETS (ROA) AT THE LISTED BANKING COMPANY IN INDONESIA STOCK EXCHANGE (BEI) BRANCH BATAM - Jurnal Ilmiah Manajemen UPB (Universitas Putera Batam, 2017)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Operation Expenses to Operations Income (BOPO), Net Interest Margin (NIM) to Return On Assets (ROA). The existing data in this research is secondary data, that is banking company in Bursa Efek Indonesia. The number of samples used are 22 commercial banks listed in Indonesia Stock Exchange with period 2011-2015 taken through purposive sampling. The method of analysis used in this study is to use multiple regression analysis that has previously done the classical assumption test first. Analyzer used in this research consist of classical assumption test, that is normality test, multicolinierity test, heteroskedasticity test, autocorrelation test and multiple linear regression analysis, that is determination test, T test and F test.The result of the test in this research shows that the variable of Capital Adequacy Ratio partially significant effect on Return On Assets with a significance value of 0.001 is smaller than 0.05. Loan to Deposit Ratio variable partially no effect on Return On Assets with significance value 0.422 greater than 0.05. Non Performing Loan variable partially significant to Return On Assets with significant value 0,003 less than 0,05 and Variable Operation Expenses to Operation Income partially significant to Return On Assets with significant value 0.000 less than 0,05. Together Capital Adequacy Ratio, Loan to Deposit Ratio, Non Performing Loan and Operation Expenses to Operations Income jointly significant effect on Return On Assets with significant value 0.000 smaller than 0.05. From R Square test result (R2) is 26,4% indicating that there is still 73,6% remaining explained by other variable not included in this research model.